THEORIES OF THE ORIGIN OF BILIARY ATRESIA (World Bulletin of Public Health, 2022)
The exact causes of biliary atresia have not yet been determined. Theories such as viral, autoimmune, genetic, toxic, and congenital malformations have been put forward by experts, but they are still controversial, despite extensive scientific research. Although viruses are considered to be a major factor in the pathogenesis of the disease, the fact that viral DNA has not been identified in patients with BA denies that viruses are the complete cause of the disease. Although the role of autoimmune factors is predominant in the origin of such BAs, other authors disagree. According to the theory of congenital malformations, it is assumed that there are no primary epithelial channels in the embryonic period. However, the majority of children with BA have bile-stained meconium, which precludes the theory of congenital development, suggesting the presence of primary normal bile ducts. Although the occurrence of the disease in both twins confirms the genetic theory, the development of BA may confirm the possibility of a secondary origin as a result of viral, toxic and other factors affecting the fetus in the same way.
Keywords: Biliary Atresia; Cholestasis; Obliteration Fibrosis; Cirrhosis